2016
DOI: 10.1097/mca.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statin therapy on plaque regression following acute coronary syndrome

Abstract: Intensive statin therapy duration over 6 months may be as important as achieved LDL-C of less than or equal to 70 mg/dl in plaque regression following ACS. Intensive statin treatment may lead to an earlier regression compared with low-dose statin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
12
0
3
Order By: Relevance
“…The JAPAN-ACS study demonstrated that statin administration significantly inhibits coronary atherosclerosis only following 8 to 12 months of treatment [ 45 ]. A previous meta-analysis also reported that high-intensity statin treatment does not result in plaque regression during the first 3 months in ACS patients; however, plaque regression occurred after 6–12 months and persisted for more than 12 months [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The JAPAN-ACS study demonstrated that statin administration significantly inhibits coronary atherosclerosis only following 8 to 12 months of treatment [ 45 ]. A previous meta-analysis also reported that high-intensity statin treatment does not result in plaque regression during the first 3 months in ACS patients; however, plaque regression occurred after 6–12 months and persisted for more than 12 months [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее высокую эффективность при этом показывают режимы высокой интенсивно-сти использования этих препаратов. По данным мета-анализа Tang X, et al [40], именно высокие дозы ста-тинов вызывали статистически значимый регресс атеромы (стандартизованная разница средних: -0,27; 95% ДИ: -0,43 до -0,12; р=0,0006) через 6 мес. тера-пии.…”
Section: влияние на маркеры воспаленияunclassified
“…Критерием протеинурии было отношение "белок мочи/креатинин мочи" 500-5000 мг/г. Паци-енты рандомизировались к аторвастатину 80 мг/сут., розувастатину 10 мг/сут., розувастатину 40 По объединенным данным исследований PLANET I и PLANET II аторвастатин, в отличие от розуваста-тина, снизил уровень протеинурии на 18% от исход-ного уровня; р=0,0003, уровень СКФ значимо не снижался: -1,67 мл/мин/1,73 м 2 ; р=0,097. Также был проведен post hoc анализ исследования PLANET I, в ходе которого было оценено влияние терапии ато-рвастатином на уровень СКФ, определяемое на осно-вании уровня цистатина С. Данный анализ также показал безопасность терапии аторвастатином в дозе 80 мг/сут.…”
Section: передовая статья обзор литературыunclassified
“…Statin's role is substantial in CAD treatment and has been well described in numerous studies [12,13]. The major, dose-dependent effect of treatment is low-density lipoprotein (LDL) cholesterol lowering through inhibiting hepatic cholesterol synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Statins also decrease triglyceride serum level and increase high-density lipoprotein (HDL) cholesterol serum level, but this effect is achievable with higher doses. Intensive treatment may reduce the volume of coronary artery atherosclerotic plaques and change their composition [13,14]. Statin pleiotropic action is based on isoprenoid inhibition and influences numerous signaling pathways.…”
Section: Introductionmentioning
confidence: 99%